2017
DOI: 10.1001/jama.2017.13890
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Use of Antithrombotic Medication and Hematuria-Related Complications

Abstract: Among older adults in Ontario, Canada, use of antithrombotic medications, compared with nonuse of these medications, was significantly associated with higher rates of hematuria-related complications (including emergency department visits, hospitalizations, and urologic procedures to manage gross hematuria).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 39 publications
1
32
2
2
Order By: Relevance
“…The well-established risk of bleeding complications during NOAC therapy was indeed reflected in the signals produced by the screening. With regard to bleeding type, NOAC therapy seemed to be associated with an increased risk of especially gastrointestinal bleeding and hematuria, which corresponds well with the findings of prior studies [4,5,26]. However, the specific results may be biased by treatment choices made in patients with a bleeding event in the period leading up to NOAC initiation (i.e.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The well-established risk of bleeding complications during NOAC therapy was indeed reflected in the signals produced by the screening. With regard to bleeding type, NOAC therapy seemed to be associated with an increased risk of especially gastrointestinal bleeding and hematuria, which corresponds well with the findings of prior studies [4,5,26]. However, the specific results may be biased by treatment choices made in patients with a bleeding event in the period leading up to NOAC initiation (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…To date, most studies based on such observational data provide associations between NOAC use and specific AEs already known from the clinical trials, e.g. bleeding related AEs [3][4][5]. However, another and complementary use of observational data when exploring AEs is hypothesis-free computerized screening of large scale health care registries.…”
Section: Introductionmentioning
confidence: 99%
“…Mogelijk zorgden de patiënten met DOAC voor het wat hogere percentage nabloedingen in het huidige onderzoek. Ander, grootschalig onderzoek (niet na een TURP) wijst eveneens op een relatie tussen DOAC en het optreden van een bloeding [14,15]. 5 % van de patiënten werd na de TURP opnieuw in het ziekenhuis opgenomen vanwege een secundaire bloeding.…”
Section: Discussieunclassified
“…Microhematuria is associated with the need for medical attention, with patients presenting to the emergency department as well as undergoing hospitalization and urologic procedures. 76 It has been shown that patients taking anticoagulant drugs are more likely to develop microhematuria than those receiving antiplatelet treatment. Warfarin is associated with the highest risk of microhematuria, while dabigatran, with a higher risk of gross hematuria than clopidogrel or aspirin.…”
Section: Surgical Treatmentmentioning
confidence: 99%